The Effect of Wind Power Generation on Distance Relay Performance - Adrianti Adrianti; Syndy Maiyunis Firdaus; Muhammad Nasir (Electrical Engineering Dept, Engineering Faculty, Universitas Andalas, 2022)
Wind Power Plants utilize induction generators to generate electrical power. This type of generator produces less short circuit current than synchronous generators; hence it may affect the operation of transmission line protection relays. This research aims to analyze the effect of a large-scale wind power plant connected to the transmission line on the performance of the distance relays. The study utilizes a simulation method using Digsilent Powerfactory on IEEE 5 bus test system. The performance of the distance relays is compared between the original system, and the system in one of its generators is replaced with a wind turbine generator. The simulations are carried out for 3-phase faults that consist of bolted short circuits, 1-ohm fault resistance and 10-ohm fault resistances. The results show that the relays performances in zone 1 are the same for all types of generations. For zones 2 and 3, depending on the relay's position, the reaches may increase or decrease when the generator is replaced by wind power. The increasing reach of the relays is due to the dropping of infeed effect felt by the relay after installation of wind power. While the decreasing reaches of some relays because they see less fault current from the wind generation. The other relays do not experience any changes. Fault resistances cause all relays to experience reduced reach.